Evolution of interspecies unilateral incompatibility in the relatives of Arabidopsis thaliana - Ling Li; Bo Liu; Xiaomei Deng; Hainan Zhao; Hongyan Li; Shilai Xing; Della D. Fetzer; Mengya Li; Mikhail E. Nasrallah; June B. Nasrallah; Pei Liu (Molecular Ecology, 2018)
The evolutionary concurrence of intraspecies self‐incompatibility ( SI ) and explosive angiosperm radiation in the Cretaceous have led to the hypothesis that SI was one of the predominant drivers of rapid speciation in angiosperms. Interspecies unilateral incompatibility ( UI ) usually occurs when pollen from a self‐compatible ( SC ) species is rejected by the pistils of a SI species, while the reciprocal pollination is compatible ( UC ). Although this SI × SC type UI is most prevalent and viewed as a prezygotic isolation barrier to promote incipient speciation of angiosperms, comparative evidence to support such a role is lacking. We show that SI × SI type UI in SI species pairs is also common in the well‐characterized accessions representing the four major lineages of the Arabidopsis genus and is developmentally regulated. This allowed us to reveal a strong correlation between UI strength and species divergence in these representative accessions. In addition, analyses of a SC accession and the pseudo‐self‐compatible ( psc ) spontaneous mutant of Arabidopsis lyrata indicate that UI shares, at least, common pollen rejection pathway with SI . Furthermore, genetic and genomic analyses of SI × SI type UI in A. lyrata × A. arenosa species pair showed that two major‐effect quantitative trait loci are the stigma and pollen‐side determinant of UI , respectively, which could be involved in heterospecies pollen discrimination. By revealing a close link between UI and SI pathway, particularly between UI and species divergence in these representative accessions, our findings establish a connection between SI and speciation. Thus, the pre‐existence of SI system would have facilitated the evolution of UI and accordingly promote speciation.